A new perspective on the regulation of neuroinflammation in intracerebral hemorrhage: mechanisms of NLRP3 inflammasome activation and therapeutic strategies - He, Kai-long; Yu, Xian; Xia, Lei; Xie, Yan-dong; Qi, En-bo; Wan, Liang; Hua, Xu-ming; Jing, Chao-hui (Frontiers in Immunology, 2025)
Intracerebral hemorrhage (ICH), a specific subtype within the spectrum of stroke disorders, is characterized by its high mortality and significant risk of long-term disability. The initiation and progression of neuroinflammation play a central and critical role in the pathophysiology of ICH. The NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, a protein complex involved in initiating inflammation, is the central focus of this article. Microglia and astrocytes play critical roles in the inflammatory damage process associated with neuroinflammation. The NLRP3 inflammasome is expressed within both types of glial cells, and its activation drives these cells toward a pro-inflammatory phenotype, which exacerbates inflammatory damage in the brain. However, the regulatory relationship between these two cell types remains to be explored. Targeting NLRP3 inflammasomes in microglia or astrocytes may provide an effective approach to mitigate neuroinflammation following ICH. This article first provides an overview of the composition and activation mechanisms of the NLRP3 inflammasome. Subsequently, it summarizes recent research findings on novel signaling pathways that regulate NLRP3 inflammasome activity. Finally, we reviewed recent progress in NLRP3 inflammasome inhibitors, highlighting the clinical translation potential of certain candidates. These inhibitors hold promise as innovative strategies for managing inflammation following ICH.